Answer:
y = − 1
Hope this helps!
Step-by-step explanation:
Alright so this is our equation:
y − 3 = 2 ( x − 1 )
We will substitute:
x = − 1
So now our equation looks like this:
y − 3 = 2 ( −1 − 1 )
Now we will get rid of the parentheses:
y − 3 = − 2 − 2
Solve the left side:
y − 3 = − 4
Now add 3 on both sides to find out what y is:
y − 3 = − 4
+3 +3
Add:
y = − 1
Yay! We found our answer! Nice job everyone!
Answer:
= 8.25
Step-by-step explanation:
6, 8, 8.5, 11
The middle number are 8 and 8.5
We then add them and divide by 2
= 8 + 8.5 / 2
= 16.5/2
= 8.25
Answer:
2
Step-by-step explanation:
2 tuijnbb
Answer:
15p+15
Step-by-step explanation:
3(3p+5)-6p+3p(5-1)
9p+15-6p+3p(4)
9p-6p+15+12p
3p+12p+15
15p+15
Answer:
Rows 126
last row has 41
last row is not full because its an odd number
Step-by-step explanation: